The diagnostic accuracy of non-invasive fetal RhD genotyping by using cell-free fetal DNA in maternal plasma - Sinem Yalcintepe; Fatma Silan; Ozturk Ozdemir; Cisem Akurut (SERNEV, 2019)
Introduction: The non-invasive prenataldiagnosis of the fetus RhD genotype in RhD incompatibility has a crucial rolein the prevention of increased anti-D immunoglobulin therapy for haemolyticdiseases in pregnant women carrying RhD negative fetus. It was aimed to detectfetal RhD genotyping by using maternal circulating cell-free DNA in the currentstudy.Methods: Maternal blood samples werecollected in different trimester of pregnancies (12-40 weeks) in 12 D-negativemothers. Cell-free fetal DNA was extracted from 2 ml of maternal plasma by anconventional DNA isolation technique (Qiagen, Hilden, Germany) and real-timePCR was performed for genotyping target RhD exons 7 and 10 and GLO genes.Postnatal serological evaluations were performed and the results wereconfirmed.Results: 6 cases (50 %)were determined D positive and 6 cases (50 %) were determined D negative. Allresults were also confirmed after birth serologically.Conclusions: In conclusion,the current results showed us the non-invasive target RhD genotyping from cellfree fetal DNA from maternal plasma samples have a diagnostic accuracy in RhDincompatibility pregnancies.